DONAT REBUNG AMPEL (BAMBUSA VULGARIS) UNTUK MENDUKUNG DIVERSIFIKASI PANGAN LOKAL - Kadek Lina Sukasri Putri (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2025)
This study aims to describe: 1) the formulation of ampel bamboo shoot (Bambusa vulgaris) doughnuts to support local food diversification, and 2) the level of preference for ampel bamboo shoot (Bambusa vulgaris) doughnuts to support local food diversification. Ampel bamboo shoot is a local food with high nutritional content, especially rich in fiber, which enhances the nutritional value of doughnuts. In every 100 grams, it contains approximately 25 kcal energy, 0.8 g protein, 5.3 g carbohydrates, and 9.7 g dietary fiber. This quantitative descriptive study used an experimental method with a hedonic test panel of 50 general public consumer panelists. Data were collected via an observation sheet measuring community preference using a Likert scale. The results show that: 1) a good formulation for ampel bamboo shoot (Bambusa vulgaris) doughnuts to support local food diversification was obtained after two experimental processes, and 2) the panelists' level of preference for ampel bamboo shoot (Bambusa vulgaris) doughnuts to support local food diversification was reviewed from five aspects, namely: color aspect with a score of 4.94, texture aspect with a score of 4.88, aroma aspect with a score of 4.92, taste aspect with a score of 4.62, and shape aspect with a score of 4.86. Based on the average scores, the ampel bamboo shoot (Bambusa vulgaris) doughnut product to support local food diversification falls into the category of highly liked.